Adam's alternative sports day : an Asperger story - Welton, Jude (Jessica Kingsley Publishers, 2005)
Adam, a nine-year-old boy with Asperger's syndrome, competes at his school's "alternative sports day," which includes puzzles, riddles, and a treasure hunt instead of races